Childbirth Induced Posttraumatic Stress Syndrome: A Systematic Review of Prevalence and Risk Factors - Dekel, Sharon; Stuebe, Caren; Dishy, Gabriella (Frontiers in Psychology, 2017)
Background. Posttraumatic stress related with the childbirth experience of full-term delivery with health outcomes has been recently documented in a growing body of studies. The magnitude of this condition and the factors that might put a woman at risk for developing childbirth-related postpartum posttraumatic stress disorder (PP-PTSD) symptoms are not fully understood. Methods. In this systematic review of 36 articles representing quantitative studies of primarily community samples, we set to examine PP-PTSD prevalence rates and associated predictors with a focus on the role of prior PTSD and time since childbirth. Results. A significant minority of women endorsed PP-PTSD following successful birth. Acute PP-PTSD rates were between 4.6% and 6.3%, and endorsement of clinically significant PP-PTSD symptoms was identified in up to 16.8% of women in community samples of high quality studies. Negative subjective experience of childbirth emerged as the most important predictor. Endorsement of PTSD before childbirth contributed to PP-PTSD; nevertheless, women without PTSD also exhibited PP-PTSD, with acute rates at 4.6%, signifying a new PTSD onset in the postpartum period. Conclusion. Although the majority of women cope well, childbirth for some can be perceived as a highly stressful experience and even result in the development of PP-PTSD symptoms. More research is needed to understand postpartum adaption and childbirth-related posttraumatic stress outcomes.